Former Yugoslav Republic of Macedonia : Staff Report for the 2009 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Former Yugoslav Republic of Macedonia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This 2009 Article IV Consultation highlights that the Former Yugoslav Republic of Macedonia's vulnerability at the outset of the global crisis was its large current account deficit in the context of the exchange rate peg to the euro. At the same time, it benefited from a small fiscal deficit, modest public debt, and significant international reserve buffers. Executive Directors have praised the Macedonian authorities for the conduct of macroeconomic policies, which contributed to a modest downturn in Macedonia's economy relative to other countries in the region.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet